Behavioral and complexity macroeconomics - Michael Roos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
This paper sketches the history of behavioral macroeconomics and presents four current approaches in the literature: the ad hoc behavioral approach, partial behavioral macroeconomic models, experimental macroeconomics, and behavioral DSGE models. Much of this literature is still patchwork, with a focus on isolated aspects but little theoretical integration. I argue that integrating behavioral features into New Keynesian DSGE models is not convincing because of fundamental problems of the DSGE approach. A better way to use research from behavioral economics for more realistic macroeconomic models is to turn to complexity economics and agent-based modeling. Complexity economics and behavioral economics are linked in a very natural way, since both emphasize the direct interaction of heterogeneous agents that are boundedly rational. Behavioral and complexity macroeconomics is a promising new approach that might make mainstream macroeconomics more realistic and relevant again.
Keywords: B41; B50; E03; C63; 330; bounded rationality; methodology; microfoundations; representative agents